The Recovery from Grade II Burns in Test Mice (Mus Musculus Linn) After Using Iodine Leaf Latex Gel (Jatropha Multifida Linn) - Saelan, Saelan; Azali, Lalu M. Panji; Rizky, Wahyu; Suryandari, Dewi (International Journal of Public Health Excellence (IJPHE), 2024)
Burn injuries are emergencies that pose a severe threat and require immediate action to save lives. The saponins, tannins, alkaloids, and flavonoids in iodine leaf latex gel (Jatropha multifida Linn) are known to speed up the healing process for burn wounds. The research aimed to investigate the effect of iodin leaf latex gel on the recovery of grade II burn wounds in male mice (Mus musculus Linn). The research employed a true-experimental laboratory method with-a-post-test-only control design group at the Kusuma Husada University Laboratory in Surakarta. A total of 24 test mice were manipulated and divided into three groups: the positive control group, the negative control group, and the iodine leaf latex gel group. Burn wounds utilized a 1,5 cm superheated mental surface applied to the backs of the mice for 5-10 seconds to induce burn injuries. The observed parameters included the burn wound area, the percentage of burn wound healing, and the duration of burn wound healing. Data analysis operated One-Way ANOVA. The research revealed that iodine leaf latex gel had a restorative time of 8 days and healing percentage of 30,75%. It was better than the other control groups. The statistical analysis indicated significance (<0,05) in the burn wound recovery percentage. In conclusion, a 6% concentration of iodine leaf latex gel had a more favorable effect on burn wound healing than other control groups.